Communal territorial rights and the role of class, race, and ethnicity in recent agrarian struggles in Latin America (2017)
Several processes have affected the regions of Latin America in recent decades: There has been an expansion of land rights based on the communalization of land tenure, which have turned into ‘territorial rights’. This produced social movements that have utilized territory as a stake in their struggles. Also, there has been an expansion of capitalist accumulation related to agribusiness and mining, associated to processes of primitive accumulation. The interplay of these processes has shaped the way contemporary social struggles have developed in rural settings. Long-term processes of capitalist accumulation have produced an overlap between land conflicts and labor disputes entailing class struggle. Even so, contemporary land rights have been increasingly significant on the basis of ethno-adscriptions. This chapter aims to stress that social classes still play an important role in the analysis of rural inequalities, but in relation with other categories such as race and ethnicity. By adopting an intersectional approach, I deploy qualitative methods to analyze the role of the social class category as entangled with race and ethnicity, within contemporary struggles over land and territory, with a special focus on the Chocó region in Colombia.